2010
DOI: 10.1016/j.appet.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes food variety? Stimulus specificity of food

Abstract: Variety is a major influence of energy intake, but it is not known how much foods have to vary to influence eating. Using a stimulus specificity habituation paradigm we assessed the influence of varying the texture and appearance of nutritionally identical foods on responding for food and energy intake, and whether sensitization, or an increase in responding prior to habituation, was related to the rate of habituation or recovery of responding. Children responded for elbow macaroni and cheese until they habitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Habituation does provide for the initial increase in responding, or sensitization, prior to the decelerating limb of the habituation curve. Because we have observed that subjects who sensitize habituate slower and consume more food than those who do not sensitize (Epstein, Robinson, Roemmich, Marusewski et al, 2010; Epstein et al, 2008), it is possible that procedures that enhance sensitization may explain more variance in energy intake than procedures that do not enhance sensitization.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Habituation does provide for the initial increase in responding, or sensitization, prior to the decelerating limb of the habituation curve. Because we have observed that subjects who sensitize habituate slower and consume more food than those who do not sensitize (Epstein, Robinson, Roemmich, Marusewski et al, 2010; Epstein et al, 2008), it is possible that procedures that enhance sensitization may explain more variance in energy intake than procedures that do not enhance sensitization.…”
Section: Discussionmentioning
confidence: 92%
“…Research suggests that habituation is influenced by stimulus specificity, such that small differences in texture, color or shape may be sufficient to recover responding to a new food (Epstein, Robinson, Roemmich, Marusewski, & Roba, 2010) and to a previously habituated food (dishabituation; Groves & Thompson, 1970; McSweeney & Swindell, 1999). Habituation is thought to relate to the cessation of a meal or satiety, though there may be processes that increase responding for food, or sensitize, before habituation begins (Epstein et al, 2008; Epstein, Temple et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that even small sensory differences, such as differences within the color or texture of foods, is enough difference in sensory variety to increase consumption [22,23]. For example, Epstein and colleagues provided elbow macaroni and cheese to children aged 8 to 12 years during a habituation task, in which children worked to have access to as much of the elbow macaroni and cheese as they desired to consume [23]. After this task was completed and children had consumed the amount of elbow macaroni and cheese they had gained access to, children could then work for access to consume the same macaroni and cheese, spiral macaroni and cheese, or chicken nuggets.…”
Section: Types Of Dietary Varietymentioning
confidence: 99%
“…People habituate to repeated presentations of the same food within a meal (1). The presentation of a novel food causes dishabituation (2), and stimulus specificity of habituation is observed for the habituating food (3). The rate of habituation to food is related to food consumption, because slower rates of habituation are associated with greater energy intake (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%